Bioactive Glasses Potential Biomaterials for Future Therapy - Kaur, Gurbinder (Series in BioEngineering, 2017)
This book describes the history, origin and basic characteristics of bioactive materials. It includes a chapter dedicated to hydroxyapatite mineral, its formation and its bioactive properties. The authors address how cytotoxicity is a determining step for bioactivity. Applications of bioactive materials in the contexts of tissue regeneration, bone regeneration and cancer therapy are also covered. Silicate, metallic and mesoporous glasses are described, as well as the challenges and future prospects of research in this field.